Mir143-BBC3 cascade reduces microglial survival via interplay between apoptosis and autophagy: Implications for methamphetamine-mediated neurotoxicity. Issue 9 (1st September 2016) - Zhang, Yuan; Shen, Kai; Bai, Ying; Lv, Xuan; Huang, Rongrong; Zhang, Wei; Chao, Jie; Nguyen, Lan K.; Hua, Jun; Gan, Guangming; Hu, Gang; Yao, Honghong
ABSTRACT: BBC3 (BCL2 binding component 3) is a known apoptosis inducer; however, its role in microglial survival remains poorly understood. In addition to the classical transcription factor TRP53, Mir143 is involved in BBC3 expression at the post-transcriptional level. Here, we identify unique roles of Mir143 -BBC3 in mediating microglial survival via the regulation of the interplay between apoptosis and autophagy. Autophagy inhibition accelerated methamphetamine-induced apoptosis, whereas autophagy induction attenuated the decrease in microglial survival. Moreover, anti-Mir143 -dependent BBC3 upregulation reversed the methamphetamine-induced decrease in microglial survival via the regulation of apoptosis and autophagy. The in vivo relevance of these findings was confirmed in mouse models, which demonstrated that the microinjection of anti-Mir143 into the hippocampus ameliorated the methamphetamine-induced decrease in microglia as well as that observed in heterozygous Mir143 +/− mice. These findings provide new insight regarding the specific contributions of Mir143 -BBC3 to microglial survival in the context of drug abuse.